A catalog of the types of Mycetophilidae (Insecta, Diptera) deposited in the Museo Argentino de Ciencias Naturales, Buenos Aires - Bachmann, A.O. (2011)
The types (only paratypes) of 102 species of Mycetophilidae described and deposited in this Museum by Dr. José Pedro Duret are recorded. A selection from his rich collection was also here deposited by him. Most of his collection was acquired by Dr. Loic Matile, Paris, France. The Museum houses no other types of species of this family.